Analisis Postur Kerja Terhadap Keluhan Musculoskeletal Disorders (MSDs) Menggunakan Metode Rapid Upper Limb Assessment (RULA) Pada Pekerja Pencantingan Di Tatsaka Batik Banyuwangi - Febrianti, Putri Amelia; Arismawati, Paramaditya; Wahyuni, Ayu Endah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Banyuwangi, as one of the cities in Indonesia, has a large and growing number of batik craftsmen, currently with 60 batik businesses. One of the crucial stages that requires high skills but also physical endurance is the pecantingan stage. In the pecantingan stage of the production process, workers sit on small chairs with their backs and necks bent. There are indications that the effectiveness of work in this stage is seen in less than optimal activities where workers often complain of fatigue. UD Tatsaka Batik is a home-based trading business in Tampo Village, Cluring District, Banyuwangi Regency, which is engaged in textiles with a daily production capacity of around 35 to 400 pieces of batik. UD Tatsaka produces four types of batik, namely, written batik, semi-written batik, semi-coloured batik, and printed batik. Therefore it is necessary to evaluate the posture of workers in this manual work as well as the large production volume. Evaluation methods include the use of the Nordic Body Map (NBM) Questionnaire Sheet to identify body complaints and the Rapid Upper Limb Assessment (RULA) method to assess work posture risks. Using the RULA method due to the use of body areas that dominate the upper body area. The results show that workers experience complaints mainly in the lower neck area, right arm, and right wrist. Workers' scores on Likert Scale 3 using the NBM questionnaire show a significant level of complaints, with scores between 71 and 77. All workers on Action Level 3 of the RULA method calculation, showing a moderate level of risk. Muscle stretching is proposed as a practical and economical solution to reduce muscle tension, easily implemented into workers' routines without disrupting the work process. This solution is expected to reduce the risk of musculoskeletal complaints and increase productivity at UD Tatsaka Batik Banyuwangi.